West Virginia - Brown, Jonatha A. (Milwaukee, WI Gareth Stevens Publishing, 2007)
West Virginia separated from Virginia to become the thirty-fifth state in 1863. West Virginia started out as part of the original Virginia Colony established by the British in the early 1600s.
5 - 9
Keywords: West Virginia; Portraits of the States